Penerapan Model Gordon dalam Pembelajaran Menganalisis Struktur Puisi pada Siswa Kelas X SMK NU Al-Qur`aniyah Tahun Ajaran 2024/2025 - Ita Erlita; Muhammad Sholeh; Ade Hasanudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The author's concern about the low ability of SMK NU Al-Qur`aniyah students in the 2024/2025 academic year in learning to analyze poetry structures and the limitations of teachers in designing effective learning models to improve students' skills in analyzing poetry structures is the background for this research. One effort that can be done is by applying the Gordon model in learning to analyze poetry structures. This study aims to determine and describe learning activities to analyze poetry structures by applying the Gordon model to class X students of SMK NU Al- Qur`aniyah in the 2024/2025 academic year and to test the effectiveness of the Gordon model in learning to analyze poetry structures in class X students of SMK NU Al Qur`aniyah in the 2024/2025 academic year. This study uses an experimental method with a nonequivalent control group design. The population of this study was all class X students of SMK NU Al-Qu`aniyah in the 2024/2025 academic year. By using saturated sampling technique, X TKJ was designated as the experimental class with 24 students and class X TSM as the control class with 20 students. The research data were collected through observation and written tests. Based on the analysis of observational data, it is proven that the implementation of the Gordon model can increase student activeness in the learning process of analyzing poetry structure in grade X students of SMK NU Al-Qur'aniyah in the 2024/2025 academic year. Based on the results of statistical calculations using the two-independent t-test (independent samples test), the calculated t was 2.620 and the t table was 2.018. Therefore, t (2.620) > t (2.018), this indicates that H_(1) is accepted and H_(0) is rejected. Thus, it can be stated that the Gordon model is effective in learning to analyze poetry structure in grade X students of SMK NU Al-Qur'aniyah in the 2024/2025 academic year.